Fumaric acid esters promote neuronal survival upon ischemic stress through activation of the Nrf2 but not HIF-1 signaling pathway - Lin-Holderer, Jiemeng; Li, Lexiao; Gruneberg, Daniel; Marti, Hugo; Kunze, Reiner (Neuropharmacology, 2016)
Oxidative stress is a hallmark of ischemic stroke pathogenesis causing neuronal malfunction and cell death. Up-regulation of anti-oxidative genes through activation of the NF-E2-related transcription factor 2 (Nrf2) is one of the key mechanisms in cellular defense against oxidative stress. Fumaric acid esters (FAEs) represent a class of anti-oxidative and anti-inflammatory molecules that are already in clinical use for multiple sclerosis therapy. Purpose of this study was to investigate whether FAEs promote neuronal survival upon ischemia, and analyze putative underlying molecular mechanisms in neurons. Murine organotypic hippocampal slice cultures, and two neuronal cell lines were treated with dimethyl fumarate (DMF) and monomethyl fumarate (MMF). Ischemic conditions were generated by exposing cells and slice cultures to oxygen-glucose deprivation (OGD), and cell death was determined through propidium iodide staining. Treatment with both DMF and MMF immediately after OGD during reoxygenation strongly reduced cell death in hippocampal cultures ex vivo. Both DMF and MMF promoted neuronal survival in HT-22 and SH-SY5Y cell lines exposed to ischemic stress. DMF but not MMF activated the anti-oxidative Nrf2 pathway in neurons. Accordingly, Nrf2 knockdown in murine neurons abrogated the protective effect of DMF but not MMF. Moreover, FAEs did not activate the hypoxia-inducible factor (HIF) pathway suggesting that this pathway may not significantly contribute to FAE mediated neuroprotection. Our results may provide the basis for a new therapeutic approach to treat ischemic pathologies such as stroke with a drug that already has a broad safety record in humans.